Change of feeding strategy prior to migration: a comparative diet analysis in the Lesser Kestrel (Falco naumanni). (1st February 2017) - Bounas, Anastasios; Sotiropoulos, Konstantinos
Assessing the variation in diet composition of a species, over different years and between periods, offers insights to comprehend its ecological niche as well as to define different feeding strategies. We studied the diet of the Lesser Kestrel (Falco naumanni) by analysing 1040 regurgitated pellets collected in the city of Ioannina (northwestern Greece). We compared diet composition between the breeding period (data from years 2010–2015) and the pre-migration period (data from 2013–2015) at the study site. A total of 8920 prey items were identified and classified into 13 different prey families. The Lesser Kestrel shows a consistent pattern of diet composition throughout years, displaying significant differences between breeding and pre-migration periods. The diet is rather diverse during the breeding season (Levins' diet breadth, B = 4.12) and is composed mainly of Orthoptera and Coleoptera, while during pre-migration, the species shows a more narrow diet breadth (B = 1.98) and feeds more often and on larger amounts of Orthoptera. These results indicate a specialised feeding strategy during pre-migration. In addition, the examination of the Orthoptera consumption during this period indicates a peak in the abundance of grasshoppers (Acrididae) in the second half of August. We suggest that at this time birds exploit high elevation open grasslands around the roosting site where grasshopper abundance is high. Thus, such areas are of high conservation importance as Lesser Kestrels depend on this localised abundance of Orthoptera in order to fuel up before their trans-Saharan migration.